ANALISIS PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN PRODUK RAJUTAN PADA CV. EKA JAYA MANDIRI - Agus Shiddiq Rachmatullah Soetiman; M. Yudi Indriawan; Riswan Panji Pratomo (JURNAL EKONOMI PERJUANGAN, 2026)
This study examines Instagram social media as the independent variable and purchasing decisions as the dependent variable. The objective of the research is to determine the influence of Instagram social media on purchasing decisions. The study was conducted at CV. Eka Jaya Mandiri. Purchasing decisions are an inherent aspect of consumer behavior. Numerous factors can trigger and influence consumers when making decisions to purchase products or services, one of which is Instagram social media. Data were collected from 88 respondents using a questionnaire. Descriptive and verificative analysis methods were employed. The results indicate that the influence of Instagram social media on purchasing decisions stands at 69,6%. In conclusion, to increase the likelihood of consumers making purchasing decisions, CV. Eka Jaya Mandiri should improve its management of Instagram social media so that its influence becomes more significant in driving consumer purchasing decisions regarding its products.